Maisy's Snowy day - Cousin,Lucy (London Walker Books Ltd, 2023)
It's a snow day! Join Maisy and her friends for a flurry of fun in this festive Maisy First Experiences book. Wrap up warm to throw snowballs and catch snowflakes, build a snow mouse, set off on a sledge race and drink a delicious mug of hot chocolate
Keywords: English fiction picture story book